Perancangan Aplikasi Evaluasi Kinerja Berdasarkan Kerangka Kerja TOGAF ADM Untuk Membangun Tata Kelola Teknologi Informasi - N. Tri Suswanto Saptadi; Hans Christian Marwi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2015)
The design of an interface model is expected to contribute in creating a system that improves effective and efficient IT Governance. Hospital as a public facility in health field requires an interface system to communicate to stakeholders. Services performance evaluation interface model is one of the fundamental requirements for strategic development of IT Governance in the future. The presence of current cloud computing technology is a solution in supporting operations in the hospital. The challenge is how hospitals can adopt these technologies. An effective strategy derives from services performance evaluation results so that the use of technology can create efficient IT Governance in terms of financial. Mapping business alignment with IT strategy needs to be done especially in the selection of cloud-based service provider outsource. The method used to adopt cloud computing architecture was referenced to one of the IT Governance international standards which is TOGAF ADM. System architecture models include interface design, infrastructure management, classification, definition, and connectivity design. The main components include business architecture, information (data), application, and technology.